2021
DOI: 10.1111/joa.13502
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of short‐period and long‐period incremental markings in porcine enamel and dentine—Results of a fluorochrome labelling study in wild boar and domestic pigs

Abstract: Zander & Hürzeler, 1958). As a result, enamel, dentine and cementum exhibit characteristic incremental markings that constitute a permanent record of the growth process for the respective tissue, analogous to the growth rings of trees (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 84 publications
1
26
0
Order By: Relevance
“…The present paper is a follow-up study to a previous investigation (Emken et al, 2021) in which we established the periodicities of enamel and dentinal growth marks in fluorochrome-labelled mandibular molars of pigs. Based on these findings, the aim of the present study was to compare crown growth parameters of mandibular second molars from wild boar and domestic pigs.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…The present paper is a follow-up study to a previous investigation (Emken et al, 2021) in which we established the periodicities of enamel and dentinal growth marks in fluorochrome-labelled mandibular molars of pigs. Based on these findings, the aim of the present study was to compare crown growth parameters of mandibular second molars from wild boar and domestic pigs.…”
mentioning
confidence: 85%
“…Based on the previously established daily periodicity of laminations in porcine enamel (Emken et al, 2021), the present study, for the first time, provides comprehensive data on second molar crown formation below). The stage of dental development recorded radiographically at the time of death in the Linderöd pigs of our study matches quite well with that reported for other domestic pig breeds at an age of about 11 months (Ide et al, 2013;Robinson et al, 1987).…”
Section: Crown Formation Time and Enamel Extension Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, cross-striations in the enamel were interpreted as daily increments of growth 54,55 . In every specimen, enamel cross-striations were aligned into clearly visible growth laminations, which have a daily periodicity 37,56 . The neonatal line in the enamel was identified as a prominent, Zn-enriched 35 accentuated line formed by discontinuities in the enamel prisms.…”
Section: Methodsmentioning
confidence: 99%
“…Lines of von Ebner are dentinal growth lines recorded in most amniote groups (Erickson, 1996a(Erickson, , 1996b. Since these incremental lines are formed through the daily mineralization of dentine in apparent response to circadian biorhythms, each line reflects the daily formation of dentine by odontoblasts (Emken et al, 2021;Erickson, 1996aErickson, , 1996b. This particular growth pattern provides the means to study tooth development and replacement in extinct vertebrates.…”
Section: The Absence Of Von Ebner Lines In the Dentinementioning
confidence: 99%